2017
DOI: 10.1128/mbio.00625-17
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering MCR-2 Colistin Resistance

Abstract: Antibiotic resistance is a prevalent problem in public health worldwide. In general, the carbapenem β-lactam antibiotics are considered a final resort against lethal infections by multidrug-resistant bacteria. Colistin is a cationic polypeptide antibiotic and acts as the last line of defense for treatment of carbapenem-resistant bacteria. Very recently, a new plasmid-borne colistin resistance gene, mcr-2, was revealed soon after the discovery of the paradigm gene mcr-1, which has disseminated globally. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(146 citation statements)
references
References 55 publications
7
129
1
4
Order By: Relevance
“…Recently, it was reported that a novel gene carried on plasmid-, mcr-2, also confers resistance to colistin [8], although it seems unusual that the mcr-2 gene is detected only in Belgium [37]. This posed a hypothesis that might be due to a mechanism for mcr-2 dissemination different from that of the paradigm mcr-1 gene.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, it was reported that a novel gene carried on plasmid-, mcr-2, also confers resistance to colistin [8], although it seems unusual that the mcr-2 gene is detected only in Belgium [37]. This posed a hypothesis that might be due to a mechanism for mcr-2 dissemination different from that of the paradigm mcr-1 gene.…”
Section: Resultsmentioning
confidence: 81%
“…The minimum inhibitory concentration (MIC) of polymyxin B was determined using a liquid broth‐dilution test as recommended by the Clinical and Laboratory Standards Institute (CLSI M100‐25; Wayne, PA, USA) with cation‐adjusted Mueller‐Hinton agar (MHA) (29, 41). Escherichia coli strain Rosetta cells expressing wild‐type (WT) MCR‐1 were the positive control, whereas the E. coli strain Rosetta transformed with null pET‐28a(+) plasmid was the negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanism of mcr ‐mediated colistin resistance; adapted from (Sun et al., ). (a) Schematic representation for LPS ‐lipid A modification by MCR ‐2 in E. coli .…”
Section: Introductionmentioning
confidence: 99%